EDUCATING FILIPINO ARCHIVISTS AMIDST THE CHALLENGES OF THE 21ST CENTURY ARCHIVAL PROFESSION - Golfo, Mary Grace P. (Journal of Philippine Librarianship; Vol 34 (2014), 2015)
As the archival profession takes off to further assert its importance in the society, it is necessary that would be archivists be equipped with the necessary understanding of the evolving archival landscape, and all other issues that go with it.